PERAN OHCHR DALAM MENANGANI KASUS ETNIK ROHINGYA - Adi Joko Purwanto (Universitas Wahid Hasyim Semarang, 2022)
This article will explain the role of one of the United Nations organizations, namely: The Office of the United Nations High Commissioner for Human Rights, commonly known as the Office of the High Commissioner for Human Rights (OHCHR) or the United Nations Human Rights Office in the case of Rohingya ethnicity in Myanmar. UN involvement in international events is absolute. As stated in the UN Charter, one of the UN's goals is to maintain international world peace and security and peacekeeping has become an instrument for the UN in achieving this goal. In this article, the author attempts to provide an overview of the role of OHCHR in Myanmar by monitoring and identifying human rights conditions in Myanmar, as well as discussing various actions taken by OHCHR to resolve the issue of inter-ethnic conflict in Myanmar. .Keywords: OHCHR, Rohingya, Ethnic Conflict, Human Right, MyanmarAbstrakArtikel ini akan menjelaskan peran salah satu organisasi Perserikatan Bangsa-Bangsa yaitu: The Office of the United Nations High Commissioner for Human Rights atau biasa dikenal dengan Office of the High Commissioner for Human Rights (OHCHR) atau Kantor Hak Asasi Manusia Perserikatan Bangsa-Bangsa dalam kasus etnis Rohingya di Myanmar. Keterlibatan PBB dalam acara internasional adalah mutlak. Sebagaimana tercantum dalam Piagam PBB, salah satu tujuan PBB adalah untuk menjaga perdamaian dan keamanan dunia internasional dan pemeliharaan perdamaian telah menjadi instrumen bagi PBB dalam mencapai tujuan tersebut. Dalam artikel ini, penulis mencoba memberikan gambaran tentang peran OHCHR di Myanmar dengan memantau dan mengidentifikasi kondisi HAM di Myanmar, serta membahas berbagai tindakan yang dilakukan OHCHR untuk menyelesaikan masalah konflik antar etnis di Myanmar. Kata kunci: OHCHR, Rohingya, Konflik Etnis, Hak Asasi Manusia, Myanmar